Answer:
E. -2, 4
Step-by-step explanation:
If the zeroes of a function are given as [tex]\alpha, \beta[/tex], then the function can be written as:
[tex](x-\alpha)(x-\beta) = 0[/tex]
Here, we are given that zeros of [tex]f(x)[/tex] are x=-1 and x=2.
As per above, we can write the function [tex]f(x)[/tex] as:
[tex](x- (-1))(x-2) = 0\\\Rightarrow (x+1)(x-2)=0[/tex]
So, [tex]f(x) =(x+1) (x-2)[/tex]
To find:
Zeroes of [tex]f(\frac{x}2)[/tex].
Solution:
We have found that [tex]f(x) =(x+1) (x-2)[/tex]
Replacing [tex]x[/tex] with [tex]\frac{x}2[/tex]:
[tex]f(\frac{x}2) =(\frac{x}2+1) (\frac{x}2-2)[/tex]
Now, Let us put it equal to 0 to find the zeroes.
[tex]f(\frac{x}2) =(\frac{x}2+1) (\frac{x}2-2) = 0\\\Rightarrow (\frac{x}2+1) = 0 \ OR\ (\frac{x}2-2) =0\\\Rightarrow \frac{x}{2} = -1\ OR\ \frac{x}{2}=2\\\Rightarrow \bold{x =-2, 4}[/tex]
So, the zeroes are -2, 4.